Utilizing Implementation Science Framework for Innovative Interprofessional Pedagogy - Kandice Porter; Monica Nandan (Academic Chairpersons Conference Proceedings, 2017)
Today’s work environments require employees to function on interdisciplinary teams. Using the implementation science framework, the presenters will describe the planning and implementation of an undergraduate curriculum model that prepares students with interprofessional competencies. They will also describe the lessons learned and potential for scaling the model with other disciplines.
Keywords: Undergraduate; Curriculum Model; Implementation Science; Interprofessional Education; Innovative Pedagogy